Impact of persistent and adolescent-limited antisocial behaviour on adult health outcomes. Issue 10 (11th April 2016) - Paradis, Angela D; Koenen, Karestan C; Fitzmaurice, Garrett M; Buka, Stephen L
Abstract : Background: Persistent engagement in antisocial behaviour across developmental periods is thought to increase the risk for early disease morbidity. However, less is known about potential adverse health outcomes among the much larger subset of individuals with antisocial behaviour limited to adolescence. Methods: Using data from the Providence, Rhode Island cohort of the Collaborative Perinatal Project, we examined the association between developmentally based subtypes of antisocial behaviour and health outcomes (n=801). Official arrest records and self-reports of engagement in antisocial behaviour were used to classify participants into antisocial groups (persistent into adulthood, adolescent-limited, no significant problems) that were contrasted across important adult health indicators. Results: With few exceptions, those with persistent antisocial behaviour had the highest prevalence of each health problem. Compared to those with no antisocial behaviour, participants with persistent problems had poorer overall health and significantly elevated odds of cardiovascular problems, wheezing, lower back pain, cancer, serious injury and emergency department visits. Those with adolescent-limited behaviour experienced significantly increased odds of health concerns including poorer overall health, hypercholesterolaemia, acute respiratory problems and wheezing, lower back pain and emergency department visits compared to participants with no antisocial behaviour. Both antisocial groups reported barriers to healthcare access. Conclusions: Findings highlight the impact of persistent antisocial behaviour on adult health, and suggest that antisocial behaviour limited to adolescence is also an important marker of poor health. Given that antisocial behaviour during adolescence is an important early marker of adverse health outcomes, youth exhibiting serious behavioural problems should be targeted for preventive interventions.